2023
DOI: 10.1101/2023.09.28.23296290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of the adjuvanted Sanofi/GSK (VidPrevtyn Beta) and Pfizer-BioNTech (Comirnaty Original/Omicron BA.4-5) bivalent vaccines against hospitalisation amongst adults aged 75 years and older in England, estimated using a test-negative case control study design

Freja Cordelia Møller Kirsebom,
Nick Andrews,
Julia Stowe
et al.

Abstract: BackgroundIn England, the Joint Committee for Vaccination and Immunisation recommended a spring 2023 booster programme for all adults aged 75 years and older and the immunosuppressed. The vaccines advised were the Sanofi/GSK AS03-adjuvanted monovalent beta variant (VidPrevtyn Beta) booster vaccine and the Pfizer-BioNTech mRNA (Comirnaty Original/Omicron BA.4-5) bivalent vaccine. This is the first time an adjuvanted COVID-19 vaccine has been administered as part of a UK COVID-19 vaccination programme. In clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Unlike the structures reported for other recombinant spike trimers, where the protein is in a closed canonical conformation with all RBD down 25 , both Sanofi vaccine antigens are in an RBD-up conformation potentially allowing the display of a broader antigenic surface. This is particularly important for the Beta trimer where the antigen shows a canonical quaternary structure with two RBD in the up position and is consistent with the similar clinical effectiveness observed in the UK Spring vaccine campaign utilizing both Sanofi Vidprevtyn Beta and Pfizer Omicron bivalent booster vaccines 32 , 33 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Unlike the structures reported for other recombinant spike trimers, where the protein is in a closed canonical conformation with all RBD down 25 , both Sanofi vaccine antigens are in an RBD-up conformation potentially allowing the display of a broader antigenic surface. This is particularly important for the Beta trimer where the antigen shows a canonical quaternary structure with two RBD in the up position and is consistent with the similar clinical effectiveness observed in the UK Spring vaccine campaign utilizing both Sanofi Vidprevtyn Beta and Pfizer Omicron bivalent booster vaccines 32 , 33 .…”
Section: Discussionsupporting
confidence: 78%
“…Here we demonstrate the Beta spike trimer in the Sanofi COVID booster vaccine has a preferential two RBD up conformation, providing twice the surface area of exposed RBD amino acids compared to the ancestral spike trimer booster vaccine. Three key mutations in the Beta spike RBD (K417N, E484A, and N501Y) are the target for two thirds of the most potent neutralizing antibodies identified from Beta SARS-CoV-2 infected individuals 32 , thus contributing to the broadly cross neutralizing immunogenicity demonstrated in the clinical development of the vaccine 12 , 13 and the real-world effectiveness against Omicron XBB.1.5 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Since completion of the RAVEN study, updated variant vaccines have been developed and have been shown to be effective as booster doses in the general population. 61,62 However, it is likely that immunocompromised and more vulnerable individuals will still not receive the same level of protection. It will be important to evaluate variant booster vaccines in subgroups of immunocompromised and vulnerable populations to identify the true effectiveness and assess the ongoing need for additional interventions for these individuals.…”
Section: Findings In Contextmentioning
confidence: 99%